Răspuns :
a . ( n -1 ) ( n -2) n = 0
fie n-2 =0 n=2 nr . 0 ,1 ,2 S= 3
fie n-1= 0 n=1 nr. - 1 ,0, 1 S=0
fie n=0 nr . -2 , -1 ,1 S= -2
b. n-2 +n -1 +n =0 ; 3n = 3 ; n=1
numerele -1 , 0 , 1 produsul=0
fie n-2 =0 n=2 nr . 0 ,1 ,2 S= 3
fie n-1= 0 n=1 nr. - 1 ,0, 1 S=0
fie n=0 nr . -2 , -1 ,1 S= -2
b. n-2 +n -1 +n =0 ; 3n = 3 ; n=1
numerele -1 , 0 , 1 produsul=0
a) (n-2)(n-1)n=0⇒unul din nr tb sa fie zero
pt n=0⇒nr sunt 0, -1, -2⇒ suma lor = s=-3
n-1=0⇒n=1⇒ nr sunt 1, 0, -1⇒s=0
n-2=0⇒n=2⇒nr sunt 0,1,2⇒s=3
b) n-2+n-1+n=0⇒3n=3⇒n=1⇒numerele sunt -1, 0,1⇒produsul=(-1)·0·1=0
pt n=0⇒nr sunt 0, -1, -2⇒ suma lor = s=-3
n-1=0⇒n=1⇒ nr sunt 1, 0, -1⇒s=0
n-2=0⇒n=2⇒nr sunt 0,1,2⇒s=3
b) n-2+n-1+n=0⇒3n=3⇒n=1⇒numerele sunt -1, 0,1⇒produsul=(-1)·0·1=0